Las pueblas fronterizas entre León y Portugal en los ss. XII y XIII: «ciudadelas» de Riba-Côa (Beira, Portugal) - Gutiérrez González, José Avelino; Benéitez González, Carmen; Larrén Izquierdo, Hortensia (Trabalhos de Antropologia e Etnologia, 2020)
.